Influence of Gender Diversity, Age, Education, and Work Experience Top Management Team on Profitability: Empirical Study on Sector Companies Banking in 2021-2023 - Andisa, Clara Cintaka; Abidin, Zaenal (Journal of Business Management and Economic Development, 2025)
This study aims to examine how the performance of national commercial banks listed on the Indonesia Stock Exchange is impacted by the gender diversity, age, education, and work experience of the Top Management Team. The sample used in this study was 47 businesses that were chosen by purposive sampling. Banking companies listed on the Indonesian Stock Exchange for the 2021–2023 period are the subject of this quantitative study. The technique used in this study is the Multiple Linear Regression method using Eview software version 12. The variables in this study are Return on Assets (Y), Gender Diversity of the Top Management Team (X1), Age of the Top Management Team (X2), Education of the Top Management Team (X3) and Work Experience of the Top Management Team (X4). The study results show that gender diversity has a positive but insignificant impact on ROA. The age variable has a positive and significant effect on ROA. The education variable has an insignificant impact on ROA. The work experience variable has a positive but not significant impact on ROA.